1928
DOI: 10.1002/ar.1090400106
|View full text |Cite
|
Sign up to set email alerts
|

The utriculo‐endolymphatic valve

Abstract: This description of a structure which, for the want of a better name, I have called the utriculo-endolymphatic valve, is based on the study of a large number of serial sections and reconstructions of human fetuses. Of the twenty-five

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1934
1934
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…At the point described however a rupture of this wall into the perilymph space appears to have occurred. No interference can be demonstrated with the patency of the communicating pathw-ays between the utricle, saccule, and ductus endolymphaticus, and the utricular fold (the possible valve-like action of which has been emphasized by Bast [11]) is seen in its normal position. The state of development of the pneumatic and marrow, spaces, the inflammatory changes in the tympanum, and the dilatation of the saccullarcavity are shown in fig.…”
Section: Left Temporal Bonementioning
confidence: 95%
“…At the point described however a rupture of this wall into the perilymph space appears to have occurred. No interference can be demonstrated with the patency of the communicating pathw-ays between the utricle, saccule, and ductus endolymphaticus, and the utricular fold (the possible valve-like action of which has been emphasized by Bast [11]) is seen in its normal position. The state of development of the pneumatic and marrow, spaces, the inflammatory changes in the tympanum, and the dilatation of the saccullarcavity are shown in fig.…”
Section: Left Temporal Bonementioning
confidence: 95%
“…Konishi69 observed that the utriculo‐endolymphatic (UE) valve opens for several days after hydrops formation begins and then closes due to the compression caused by increasing hydrops. The UE valve exists at the junction between the utricle and utricular duct 70. Because the endolymph can easily flow in the direction from the utricular duct to the utricle but not in the reverse direction, the role of the UE valve is to maintain pressure in the utricle and semicircular canals.…”
Section: Hydrops In the Inner Earmentioning
confidence: 99%
“…The protective role of the valve of Bast (that closes the utricular duct) explains this unusual situation: decreasing pressure in the whole endolymphatic system collapses the ductus reuniens and causes closure of the valve. 18 19 20 21 It is plausible that the reopening of the valve of Bast after the repair of the fistula may have let the remaining air bubbles t diffuse within the cochlea and induce total auditory loss.…”
Section: Discussionmentioning
confidence: 99%